(untitled) (PERENNIAL, 2009)
Wood deterioration were generally occured by the activities of biological agents. Fungal can attack wood and lignoselullosic substances and cause staining and decaying. Its damage levels were vary depending on the attacking fungal species. Eventhough it poses some disadvantages, actually fungy have potential benefits for human life such as nutrient, energy resources, medicine, etc. Fungy from the Hasanuddin University Experimental Forest were collected, isolated, and identified in this study. Identification was conducted throughout their macroscopic and microscopic characteristics. The result showed that the amount of fungal species were fourteen species, i.e: Trichoderma sp., Phymatotrichum sp., Pycnoporus cinnabarinus, Pleurotus sp., Verticillium sp., Schizophyllum sp., Clavariadelphus truncates, Beuveria sp, Dendryphion sp., Penicillium sp., Amanita junguilea (jamur kikik), Auricularia auricularis (jamur kuping pimir), Amanita fuliginea Hongo, and Fusarium sp. Key words: Wood fungy, deterioration, Hasanuddin University Experimental Forest